The experiences of women living with HIV and AIDS in Mankweng area, Limpopo Province - Malatji, Modjadji Linda (University of Limpopo (Turfloop Campus), 2007)
The impact of AIDS has an overwhelming effect on women as they are unable to fulfill their multiple roles. For many women, a diagnosis of HIV/AIDS carries a profound physical, psychological and social burden. Gender inequities, poverty and a growing prevalence of HIV in developing countries have increased the vulnerability of women to HIV infection. Women’s lack of social and economic independence and their low status in their marital households also increase their vulnerability to HIV. They are susceptible to stigma and discrimination when they are identified as being HIV-positive. Negative social responses in these situations may result in them being rejected by their families and denied access to resources. A qualitative exploratory-descriptive study was conducted with fifty six women living with HIV/AIDS (WLWHA) in the Mankweng area and surrounding villages. Six focus groups interviews were conducted to elicit information about their experiences and perceptions on the way families, communities, health and social service professions treat them. A quantitative approach was also used to indicate the number of participants who shared similar views on a particular issue. The striking feature about the participants’ explanation of HIV and AIDS is that, they associated HIV/AIDS with makgoma (contaminations). The participants also reported that dealing with the consequences of the disease is a huge challenge. They also face challenges in managing their illness. Their problems are compounded by accusations from their partners, family members and the community who blame them for the infection. This creates stress for them that may be detrimental to their physical and emotional health. The participants freely expressed views on HIV/AIDS, aspects that are positive and unsupportive of people living with HIV/AIDS. They shared their physical, social, psychological, cultural and economical challenges. The findings also revealed that an overwhelming number (89%) of WLWHA are struggling with negotiating for condom use. Some of their partners are reluctant to use condoms thus, risking re-infection that is detrimental to their health. The participants’ plea is for the health and social service professionals to become sensitive and compassionate towards them.
Thesis (M.A. (Social work)) --University of Limpopo, 2007
Keywords: HIV/AIDS; 616.97920968; AIDS (Disease); HIV (Virus); AIDS (Disease) -- Social aspects -- South Africa